2003
DOI: 10.1073/pnas.1635258100
|View full text |Cite
|
Sign up to set email alerts
|

Extensive regional atmospheric hydrocarbon pollution in the southwestern United States

Abstract: Light alkane hydrocarbons are present in major quantities in the near-surface atmosphere of Texas, Oklahoma, and Kansas during both autumn and spring seasons. In spring 2002, maximum mixing ratios of ethane [34 parts per 10 9 by volume (ppbv)], propane (20 ppbv), and n-butane (13 ppbv) were observed in north-central Texas. The elevated alkane mixing ratios are attributed to emissions from the oil and natural gas industry. Measured alkyl nitrate mixing ratios were comparable to urban smog values, indicating act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 132 publications
(145 citation statements)
references
References 14 publications
4
139
2
Order By: Relevance
“…With the increase in unconventional oil and natural gas has come an increase in fugitive emissions of hydrocarbons to the atmosphere in quantities great enough to influence local-and regional-scale ozone production (Katzenstein et al, 2003;Kemball-Cook et al, 2010;Edwards et al, 2014 (Schnell et al, 2009). In situ measurements revealed that the high wintertime ozone levels were due to a strong temperature inversion that trapped NO x and hydrocarbon emissions from the natural gas industry.…”
Section: Unconventional Oil and Natural Gas Productionmentioning
confidence: 99%
“…With the increase in unconventional oil and natural gas has come an increase in fugitive emissions of hydrocarbons to the atmosphere in quantities great enough to influence local-and regional-scale ozone production (Katzenstein et al, 2003;Kemball-Cook et al, 2010;Edwards et al, 2014 (Schnell et al, 2009). In situ measurements revealed that the high wintertime ozone levels were due to a strong temperature inversion that trapped NO x and hydrocarbon emissions from the natural gas industry.…”
Section: Unconventional Oil and Natural Gas Productionmentioning
confidence: 99%
“…Katzenstein et al (2003) reported elevated alkane concentrations in air samples collected at the surface in the southwestern US and attributed them to the oil and NG operations in the region. The authors also measured alkyl nitrate species, indicating enhanced photochemistry in the presence of VOC emissions and NO x .…”
Section: R Ahmadov Et Al: Understanding High Wintertime Ozone Pollumentioning
confidence: 99%
“…Kemball-Cook et al (2010) modeled the impact of the Haynesville Shale development on ambient O 3 levels in Texas and Louisiana. Their photochemical modeling of the year 2012 showed increases in 8 h average ozone values of up to 5 ppb within northeastern Texas and northwestern Louisiana resulting from development in the Haynesville Shale.…”
Section: R Ahmadov Et Al: Understanding High Wintertime Ozone Pollumentioning
confidence: 99%
“…The inflow of such emissions to Boulder, Colorado, has been suggested as the large, unidentified propane source that is important in that urban area [Goldan et al, 1995]. Katzenstein et al [2003] have shown the widespread influence of such emissions in the southwestern United States. These data fall on the trend line in Figure A3a, but appear at somewhat lower alkane to ethane ratios than the average source ratios.…”
Section: Appendix A: Photochemical Aging Pattern Of Alkanesmentioning
confidence: 99%